PENGEMBANGAN BAHAN AJAR IPAS BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS IV SD NEGERI 2 PAYA BUJOK TUNONG - Desvita Sari Siregar, Winda; Mahlianurrahman; Kumala Sari, Cut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science and Social Studies (IPAS) learning in elementary schools is still dominated by the use of instructional materials that lack contextual relevance, resulting in students’ cognitive learning outcomes on the topic of states of matter and their changes being less than optimal. This study aimed to develop Timphan local wisdom-based IPAS teaching materials that are valid, practical, and effective in improving the cognitive learning outcomes of fourth-grade students at SD Negeri 2 Paya Bujok Tunong. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 25 fourth-grade studens. Data were collected through observations, interviews, and validation sheets. The validation result showed that the teaching materials achieved a score of 90% from the material expert, 90% from the media expert, 100% from the language expert, and 92% from the assessment expert. The teaching materials were also categorized as highly pratical based on the teacher’s response score of 96% and the students’ response score of 92,64%. The effectiveness of the theaching materials was demonstrated by the increase in the average pre-test score from 54,96 to 89,64 on the post-test, with an N –Gain score of 0,7744, which falls into the high category. Therefore, the Timphan local wisdom –based IPAS teaching materials are valid, practical, and effective for improving the cognitive learning outcomes of fourth-grade student at SD Negeri 2 Paya Bujok Tunong.